Innovation Management Of The Leading Program In Improving The Quality Of Graduates (Sequential Exploratory Design Mix Method Study At MAN 2 Kudus) - Ambarwati, Ambarwati; Masrokan M, Prim; Efendi, Nur; Mu’arif , Samsul (International Journal of Educational Research & Social Sciences, 2024)
This research is motivated by the phenomenon of success of MAN 2 Kudus students who have many academic and research achievements achieved institutionally, nationally and internationally.  This success is also proven by recognition based on the publication of two Decrees of the Directorate General of Islamic Education, namely Decree of the Directorate General of Islamic Education Number 6757 of 2020 concerning the designation of MAN 2 as a research madrasa and Decree of the Directorate General of Islamic Education Number 1834 of 2021 which states that MAN 2 Kudus is a superior madrasah in the academic field. With some of this evidence, it shows that MAN 2 Kudus has good superior program innovation management so that it has an influence on improving the quality of its graduates. This research aims to find out the quality of graduates from the superior academic and research program at MAN 2 Kudus, how the initiation, implementation, support and evaluation of superior academic and research programs improve the quality of graduates and to find out whether the innovation management of superior programs has an effect on the quality of graduates at MAN 2 Kudus This type of research uses mixed methods. The population in this study were 736 students in superior program classes and teachers who taught superior program classes. The research sample was 101. The data collection techniques were questionnaires, interviews, observation and documentation. The data analysis technique used is 1) quantitative analysis using Smart PLS, 2) qualitative analysis using interactive model analysis. The results of this research conclude 1) The quality of graduates from the superior academic and research program at MAN 2 Kudus reached a score of 81.49% of what was expected. This can be stated qualitatively as good. 2) Innovation management of superior academic and research programs in improving the quality of graduates at MAN 2 Kudus is carried out by: a. Initiation of superior academic program innovation includes program formulation, human resource adjustments and setting superior standards. b. Implementation of superior academic program innovations includes: dividing programs, adding supporting materials and adjusting human resources c. The supporting capacity for innovation in superior academic and research programs includes the availability of infrastructure, the availability of educators and research supervisors and stakeholder awareness. d. Evaluation of superior academic and research program innovation is carried out by: evaluating the initiation, implementation and supporting capacity of academic and research programs. Meanwhile, quantitatively, superior program innovation management has a significant influence on the quality of graduates.